What is the Effect of Vitamin Supplements in Healthy Adults Beyond Placebo Effect? A Systematic Review of Randomized Trials - Zewdu, Mick; Holbrook, Anne; Li, Michelle; Megas, Alexander; Matos Silva, Caroline; Vishwanath, Analpa; Saini, Amitoj (My University, 2024)
There is not currently a scientific consensus on how much of the effects of such supplements are the result of placebo or nocebo effect, versus the supplement itself, in healthy individuals. Objective Our objective is to systematically review the literature for randomized placebo-controlled trials involving healthy adults and studying the effect of vitamin supplements as defined above on important health outcomes. Research Question For community-dwelling healthy adults, what is the effect of consumption of vitamin supplements beyond that of placebo on important clinical outcomes in randomized trials of at least 4 weeks follow-up?
Keywords: vitamins; placebo effect; systematic review